Perceived tax audit aggressiveness, tax control frameworks and tax planning: an empirical analysis - Kay Blaufus; Jakob Reineke; Ilko Trenn (Journal of Business Economics, 2022)
This paper examines whether a perceived increase in tax audit aggressiveness is associated with lower tax planning effort and a higher quality of internal tax control frameworks. Using survey data on corporate tax functions from approximately 200 firms from different countries, contrary to expectations, we find that neither internal nor external resources devoted to tax planning are lower for firms that perceive an increase in tax audit aggressiveness. Nevertheless, for these firms, we find a positive association with the quality of their tax control framework and their investments in the reputation management and communication skills of their tax department staff. In line with this, we find that an increase in perceived audit aggressiveness is directly (indirectly) associated with an increase in resources allocated to the tax function "controversy and audit defense" ("risk management and governance"). In addition, our results show a positive relationship between the quality of the tax control framework and the need for comprehensive improvements in human capital and internal processes, suggesting that the tax control framework affects the firms' perceptions of their tax capabilities and drives organizational changes. Overall, these findings are in line with the rationale that an increase in audit aggressiveness changes the costs of compliance errors such that firms improve the quality of their tax control framework to reduce future errors. In contrast, it remains unclear whether tax audit aggressiveness actually changes tax planning behavior, as we find no negative association with the firms' investment in tax planning.
Keywords: M40; M41; M48; H26; 650; Tax avoidance; Tax control framework; Tax enforcement; Tax compliance management